Hechos de violencia extrema y campos totalitarios senderistas entre los Ashaninka y Nomatsiguenga de la selva central del Perú - Villasante Cervello, Mariella (Pontificia Universidad Católica del Perú, 2024)
Studies on the internal war in Peru have ignored the acts of violence: recruitments, rapes, executions, massacres and totalitarian camps. From the anthropology of violence, this article exposes the central points of an ignored topic: the totalitarian Senderista camps in which thousands of Ashaninka and Nomatsiguenga natives were captives. The Shining Path leaders sought the transformation of thousands of natives who had to destroy their social identities to create a “new communist society.” The priority sources are the testimonies collected by the author between 2008 and 2017, and the testimonies collected by the CVR between 2002 and 2003. The analysis takes into account, in particular, the works of Françoise Héritier, Hannah Arendt, and Tzvetan Todorov.

Los estudios sobre la guerra interna en el Perú han soslayado los hechos de violencia extrema: reclutamientos, violaciones, ejecuciones, masacres y campos totalitarios. A partir de la antropología de la violencia, este artículo expone los puntos centrales de un tema inexplorado: los campos totalitarios senderistas en los cuales estuvieron cautivos miles de Ashaninka y Nomatsiguenga. Los dirigentes de Sendero Luminoso buscaron la transformación de miles de nativos que debían destruir sus identidades sociales para crear una “nueva sociedad comunista”. Las fuentes prioritarias son los testimonios que he recogido entre 2008 y 2017, y los testimonios recabados por la CVR entre 2002 y 2003. El análisis toma en cuenta, en particular, los trabajos de Françoise Héritier, de Hannah Arendt y de Tzvetan Todorov.
Acts of extreme violence and totalitarian Shining Path camps among the Ashaninka and Nomatsiguenga of the central jungle of Peru
Keywords: Peruvian internal war; Acts of violence; Totalitarian camps; Ashaninka; Nomatsiguenga; Shining Path; 20th century; Guerra interna peruana; Hechos de violencia; Campos totalitarios; Ashaninka; Nomatsiguenga; Sendero Luminoso; Siglo XX; https://purl.org/pe-repo/ocde/ford#6.00.00